Interaction of Some Factors in the Mechanism of Inactivation of Bacteriophage MS2 in Aerosols - Trouwborst, T. (1973)
The mechanisms involving inactivation of bacteriophage MS2 in aerosols and the effect of protective substances in the spray-medium were studied after spraying from various NaCl solutions. Results with aerosols generated from the salt solutions showed that with higher salt concentration in the spray-medium higher concentrations of protective substances were needed to protect phage MS2 against aerosol inactivation. Phenylalanine, which has a protective action at low concentration, produced less protection in aerosol droplets that were supersaturated solutions of this substance or in which crystals of phenylalanine can be expected to form. Our results suggested that protection by peptone and phenylalanine was related to the concentration in the aerosol droplet after evaporation to equilibrium, whereas protection by the surface active agent OED (a commercial mixture of oxyethylene docosylether and oxyethelene octadecylether) was related to the concentration at which a monolayer is formed around the aerosol particle. Inactivation of phage MS2 was maximal in the aerosol particle in fluid phase and became less at lower relative humidity where aerosol particles are expected to be in the solid state. It is suggested that inactivation of bacteriophage MS2 in aerosols could be explained by surface inactivation at the air-water interface.